The Influence of Digital Marketing and Consumer Behavior On Consumer Purchase Interest in Online Food Delivery Services with Social Media Marketing as a Variables Mediation - Fadhil Febriansyah (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
This study aims to explore the influence of digital marketing and consumer behavior on consumer purchasing interest in online food delivery (OFD) services, with social media marketing as a mediating variable. OFD services such as GoFood, GrabFood, and ShopeeFood have experienced rapid growth, supported by the use of digital technology and social media in marketing strategies. As the use of social media such as Instagram, Facebook, and TikTok increases, OFD companies are increasingly relying on these platforms to increase consumer engagement, spread promotions, and influence purchasing decisions. This study uses a quantitative approach with data collection through a survey of OFD service users in the Jakarta area. The sampling technique uses a purposive sampling method where the criteria are active users of OFD services. This analysis is carried out to evaluate the extent to which digital marketing, consumer behavior, and social media marketing can influence consumer purchasing interest, both directly and through mediating variables. The results of this study are expected to provide comprehensive insights into the role of digital marketing and consumer behavior in forming effective marketing strategies in the digital era, especially in the OFD industry. In addition, these findings can also help companies understand how social media marketing can be optimally utilized to increase consumer purchasing interest and strengthen brand loyalty in an increasingly competitive market.